A Systematic Review of Procedural Outcomes in Patients With Proximal Common Carotid or Innominate Artery Disease With or Without Tandem Ipsilateral Internal Carotid Artery Disease. (December 2020) - Robertson, Vaux; Poli, Federica; Saratzis, Athanasios; Divall, Pip; Naylor, A. Ross
Abstract : Objective: To establish 30 day and mid term outcomes in patients treated for significant stenoses affecting the proximal common carotid artery (CCA) or innominate artery (IA) with/without tandem disease of the ipsilateral internal carotid artery (ICA). Methods: Systematic review of early and mid term outcomes in 1 969 patients from 77 studies (1960–2017) who underwent: (i) hybrid open retrograde angioplasty/stenting of the IA/proximal CCA plus carotid endarterectomy (CEA) in patients with tandem disease of the ipsilateral proximal ICA ( n  = 700); (ii) isolated open surgery to the IA or proximal CCA (no CEA) ( n  = 686); or (iii) an isolated endovascular approach to IA or proximal CCA stenoses (no CEA) ( n  = 583). Results: In the hybrid group with tandem disease (66% involving proximal CCA), the 30 day death/stroke was 3.3%, with a late ipsilateral stroke rate of 3.3% at a median six years follow up. Late re-stenosis was 10.5% for proximal CCA/IA and 4.1% for the ICA. In the isolated open surgery group (78% involving the IA), the 30 day death/stroke was 7%, with a late ipsilateral stroke rate of 1% at a median 12 years follow up. Late re-stenosis within aortic bypasses was 2.6%. In the isolated endovascular group (52% IA, 47% proximal CCA), the majority of procedures were done percutaneously (84%), with a 30 day death/stroke rate of 1.5%. Late ipsilateral stroke was 1% at a median four years follow up, with a re-stenosis rate of 9%. Conclusion: Procedural risks were higher following isolated open surgical interventions involving the proximal CCA/IA, compared with proximal lesions treated by isolated angioplasty/stenting, or in tandem with CEA. This higher morbidity/mortality may, however, reflect a greater proportion of innominate ( vs. proximal CCA) lesions in open surgical series, changes in patient selection, time dependent evolution of medical interventions, and publication bias. The available data were limited and related to very different patient groups and management strategies spanning 57 years. Caution is raised, particularly for open surgery IA and CCA surgery, and for any procedures in asymptomatic patients. In symptomatic patients, the data cautiously support an "endovascular first" strategy for isolated proximal CCA/IA lesions and a hybrid approach for tandem proximal CCA/IA and ICA stenoses.